2018
DOI: 10.3390/agriculture8110173
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Actor Literature Review on Alternative and Sustainable Food Systems for the Promotion of Cereal Biodiversity

Abstract: Organic and low-input food systems are emerging worldwide in answer to the sustainability crisis of the conventional agri-food sector. “Alternative” systems are based on local, decentralized approaches to production and processing, regarding quality and health, and short supply-chains for products with strong local identities. Diversity is deeply embedded in these food systems, from the agrobiodiversity grown in farmers’ fields, which improves resilience and adaptation, to diverse approaches, contexts and acto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 87 publications
1
15
0
1
Order By: Relevance
“…Several studies, in fact, demonstrated that honey is a product with numerous therapeutic properties for human health that are able to prevent and/or treat certain diseases [64,65] and consumers are more and more conscious about its health and medical benefits [56,66]. This result is consistent with Sacchi et al [67] who highlighted that, nowadays, consumers are increasingly interested in food that provides health benefits by improving well-being and reducing the risk of diseases.…”
Section: Discussionsupporting
confidence: 67%
“…Several studies, in fact, demonstrated that honey is a product with numerous therapeutic properties for human health that are able to prevent and/or treat certain diseases [64,65] and consumers are more and more conscious about its health and medical benefits [56,66]. This result is consistent with Sacchi et al [67] who highlighted that, nowadays, consumers are increasingly interested in food that provides health benefits by improving well-being and reducing the risk of diseases.…”
Section: Discussionsupporting
confidence: 67%
“…Knowledge exchange via local networks makes it possible for agri-food systems to move towards adoption of a sustainable approach (Sacchi et al, 2018). Short supply chains depend on an alternative form of social organisation, which is influenced by group norms that are important preconditions for the sustainability of these alternative food networks (Charatsari et al, 2018).…”
Section: Literature Review: Network and Social Media In Sfscmentioning
confidence: 99%
“…Consumers are increasingly interested in sustainably produced food ingredients, and alternative agricultural models have emerged to emphasize factors such as diversity and environmental concerns [1]. Perennial grains have the potential to become serious contenders in the cereal market place, provided that their quality matches the requirements of manufacturers as well as expectations of consumers [2].…”
Section: Introductionmentioning
confidence: 99%